Pityriasis rubra pilaris and HIV: a diagnostic challenge-case report and critical review of the literature - Pérez-García, Mónica M.; Ortuz-Lessa, Camila; Amador-Eleuterio, Sarahi; Gallegos-Ramos, Arely L. (International Journal of Research in Medical Sciences, 2025)
Pityriasis rubra pilaris (PRP) is a rare cutaneous disorder characterized by hyperkeratotic follicular papules and palmoplantar keratoderma. Its clinical presentation ranges from mild to severe forms, including erythroderma. There are six types of PRP. Type VI is associated with HIV, presenting with a more severe and challenging course. This variant can occur in HIV-positive patients regardless of their CD4 T cell count. This article provides a detailed review of the pathogenesis, clinical characteristics, diagnosis, differential diagnosis and therapeutic options of PRP, with an emphasis on its HIV-associated form. An illustrative clinical case is presented, analyzing the underlying pathogenesis and treatments used. Furthermore, these findings are compared with those reported in the literature to provide a broader perspective on how this disease affects immunocompromised patients.